1996
DOI: 10.1155/s1064744996000087
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium sordellii Toxic Shock Syndrome: A Case Report and Review of the Literature

Abstract: Treatment modalities aimed solely at the eradication of the microbe and removal of necrotic tissue, although essential components of therapy, have proved inadequate. Future efforts should be directed toward neutralization or elimination of the circulating exotoxins responsible for the systemic shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Fisher et al, 9 Cohen Al et al 10 have reported a fatal case after abortion with mifepristone and misoprostol. Sosolik 11 et al have reported a case of primipara developing an episiotomy infection which progressed to involve the underlying fascia and muscle. Despite early and adequate debridement of the devitalized tissue, she developed anasarca, marked leukocytosis, refractory hypotension, hypothermia, and a persistent coagulopathy, and expired on postpartum day 5.…”
Section: Diagnosismentioning
confidence: 99%
“…Fisher et al, 9 Cohen Al et al 10 have reported a fatal case after abortion with mifepristone and misoprostol. Sosolik 11 et al have reported a case of primipara developing an episiotomy infection which progressed to involve the underlying fascia and muscle. Despite early and adequate debridement of the devitalized tissue, she developed anasarca, marked leukocytosis, refractory hypotension, hypothermia, and a persistent coagulopathy, and expired on postpartum day 5.…”
Section: Diagnosismentioning
confidence: 99%